1999
DOI: 10.1111/j.1349-7006.1999.tb00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Target Regions of Allelic Loss on Chromosome 9 in Urinary‐bladder Cancer

Abstract: Allelic losses on chromosome 9 are common in a wide variety of human tumors; moreover, two predisposing loci for some inherited cancer syndromes, i.e., familial malignant melanoma and Gorlin syndrome, have been identified on this chromosome. To define the location of putative tumor suppressor genes involved in cancer of the urinary bladder, 85 bladder cancers were examined for allelic loss at 18 microsatellite loci on chromosome 9. Correlations were also sought between loss of heterozygosity on chromosome 9 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…To date, additional polymorphic markers across the D9S1748-D9S126 interval are not available in the Genome Database, and thus they must be developed starting from sequenced DNA (which is now being reported in public databases). Interestingly, a high frequency of LOH at 9p21, including the D9S171 locus, has been described for other types of cancer (Ohgaki et al, 1999;Perinchery et al, 1999), again confirming that this region may harbour several tumour suppressor genes involved in carcinogenesis.…”
Section: Discussionmentioning
confidence: 71%
“…To date, additional polymorphic markers across the D9S1748-D9S126 interval are not available in the Genome Database, and thus they must be developed starting from sequenced DNA (which is now being reported in public databases). Interestingly, a high frequency of LOH at 9p21, including the D9S171 locus, has been described for other types of cancer (Ohgaki et al, 1999;Perinchery et al, 1999), again confirming that this region may harbour several tumour suppressor genes involved in carcinogenesis.…”
Section: Discussionmentioning
confidence: 71%
“…The 9q32-q33 region, in particular, has been a focus of intense research to identify a tumor suppressor gene related to the development of bladder cancers, because evidence derived from independent deletion-mapping studies of 9q have revealed common deletions in that region. For instance, we undertook a high-resolution deletion-mapping effort involving 85 primary bladder cancers, using 18 microsatellite loci on chromosome 9, and defined a commonly deleted region within 9q31-q34 in an interval flanked by D9S58 and D9S61 (Ohgaki et al 1999). One of us (Habuchi et al 1995) independently carried out deletion mapping in a different panel of primary bladder cancers, and defined a narrow, commonly deleted region at 9q32-q33 flanked by markers D9S1848 and AFMA239XA9.…”
Section: Discussionmentioning
confidence: 99%
“…However, chromosome 9 is the most frequent site of allelic loss in cancers of the bladder and urinary duct, which, together, are classified as transitional cell carcinomas (TCCs); this observation has been consistent worldwide (Olumi et al 1990;Dalbagni et al 1993;Habuchi et al 1993;Knowles et al 1994). In fact, LOH at loci on chromosome 9 has been detected in more than half of all bladder cancers examined, regardless of their grades and stages Ohgaki et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 9q12-22 region contains the human homologue of the murine growth-arrest-specific gene gas 1, and the PTCH gene, which has been suggested as a TSG in basal cell carcinoma and in bladder cancer; nevertheless mutation of PTCH in bladder TCC was found infrequently. 2,9 Using highdensity deletion mapping with a large number of microsatellites markers, Habuchi et al 10 identified a candidate TSG in bladder cancer, the DBCCR1 gene (deleted in bladder cancer chromosomal region candidate 1), located between markers D9S103 and GSN at 9q33. Expression of DBCCR1 was found downregulated in bladder cancer cells in vitro, and although no mutation has been detected in bladder tumors, DBCCR1 expression was silenced by promoter hypermethylation in 50% of bladder cancer cell lines investigated.…”
mentioning
confidence: 99%